Association of Clinical Appearance with Histopathological Features in Oral Squamous Cell Carcinoma - Varusha Sharon Christopher1 , Hannah R2, Manish Ranjan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral Squamous Cell Carcinoma (OSCC) is one of the most common malignant epithelial neoplasms affectingthe oral cavity. The clinical appearance of oral cancer is highly variable and includes ulceroproliferative,ulcerative, leukoplakic and exophytic. These clinical variants can be graded histopathologically to be a welldifferentiated, moderately differentiated or poorly differentiated squamous cell carcinoma. The prognosisof the patients varies based on the histopathological grading. Hence, the aim of the study is to associate theclinical appearance of OSCC with the histopathological grading. Data was collected after going through86,000 patients records from June 2019 to April 2020. Total sample size of the study was 44. The datawas exported to SPSS and the variables were verified. Correlation analysis was carried out for the datatabulated. Highest correlation was seen between ulceroproliferative lesions and well differentiated OSCChistopathologically. Hence we can conclude that the clinical appearance of OSCC can give us some clueabout its histopathological grade and the study should be extended to a larger sample size in order to give amore comprehensive outcome.